An easy and practical approach to access multifunctional cylcopentadiene- and cyclopentene-spirooxindoles via [3 + 2] annulation. Issue 19 (28th April 2021) - Warghude, Prakash K.; Sabale, Abhijeet S.; Dixit, Ruchi; Vanka, Kumar; Bhat, Ramakrishna G.
Abstract : A highly regioselective [3 + 2] annulation of Morita–Baylis–Hillman (MBH) carbonates of isatin with aurone/thioaurone is developed. Abstract : A highly regioselective [3 + 2] annulation of Morita–Baylis–Hillman (MBH) carbonates of isatin with aurone/thioaurone is developed. Spiroheterocycles such as spirooxindole cyclopentadiene and spirooxindole fused hydroxy cyclopentene derivatives are constructed in one pot by exploring the reactivity of Lewis bases. Combined experimental and density functional theory (DFT) calculations offered an insight into the reaction mechanism.